Model nepremičninskih in psiholoških dejavnikov odločanja za nakup nepremičnine - Grum, Bojan (Urbani izziv, 2015)
This article explores the psychological characteristics of potential real estate buyers connected with their decision to buy. Through a review of research, it reveals that most studies of psychological factors in the decision to buy real estate have a partial and dispersed orientation, and examine individual factors independently. It appears that the research area islacking clearly defined models of psychological factors in the decision to buy real estate that would integrally and relationally explain the role of psychological characteristics of real estate buyers and their expectations in relation to a decision to buy. The article identifies two sets of psychological factors, motivational and emotional, determines their interaction with potential buyers' expectations when deciding to purchase realestate and offers starting points for forming a model.
Keywords: nakup; nepremičnine; odločanje; psihologija potrošnika